A relação entre literatura de cordel e mídia: uma reflexão acerca das implicações para o gênero - Resende, Viviane de Melo (Cadernos de Linguagem e Sociedade, 2010)
In this paper, I focus the Brazilian literatura de cordel, popular literature in verse, typical of Brazilian Northeast. The paper is based on interviews, carried through between 2002 and 2004, with diverse social actors involved in the production of the cordel. The interviews were carried through in Campina Grande (PB), Caruaru, Bezerros and Recife (PE), Juazeiro do Norte and Fortaleza (CE) and in Rio de Janeiro, where there is the Brazilian Academy of Literatura de Cordel (ABLC). The objective of the paper is thinking the relations of the cordel with the media and the implications of these relations for the cordel as social and discursive practice.